2018
DOI: 10.1074/jbc.m117.816769
|View full text |Cite
|
Sign up to set email alerts
|

DeSUMOylation of MKK7 kinase by the SUMO2/3 protease SENP3 potentiates lipopolysaccharide-induced inflammatory signaling in macrophages

Abstract: Protein SUMOylation has been reported to play a role in innate immune response, but the enzymes, substrates, and consequences of the specific inflammatory signaling events are largely unknown. Reactive oxygen species (ROS) are abundantly produced during macrophage activation and required for Toll-like receptor 4 (TLR4)–mediated inflammatory signaling. Previously, we demonstrated that SENP3 is a redox-sensitive SUMO2/3 protease. To explore any links between reversible SUMOylation and ROS-related inflammatory si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 87 publications
2
49
0
Order By: Relevance
“…These enzymes include an E1 SUMO-activating enzyme, the E2-conjugating enzyme Ubc9, and an E3 ligase, such as the PIAS family proteins, RanBP2, and Pc2, which facilitate the transfer of SUMO from Ubc9 to specific target proteins ( 16 ). Previous data suggested that the conjugation of SUMO2 and SUMO3 is predominantly induced as an intracellular protective response to cellular stresses, such as hypoxia and inflammatory stimuli ( 17 ). There is also a series of reports showing a neuroprotective role of SUMOylation in brain lesions caused by ischemia-reperfusion injury ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes include an E1 SUMO-activating enzyme, the E2-conjugating enzyme Ubc9, and an E3 ligase, such as the PIAS family proteins, RanBP2, and Pc2, which facilitate the transfer of SUMO from Ubc9 to specific target proteins ( 16 ). Previous data suggested that the conjugation of SUMO2 and SUMO3 is predominantly induced as an intracellular protective response to cellular stresses, such as hypoxia and inflammatory stimuli ( 17 ). There is also a series of reports showing a neuroprotective role of SUMOylation in brain lesions caused by ischemia-reperfusion injury ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because SENP3 −/− mutation causes embryonic lethality [28] , SENP3 +/− mice were generated. To further define the in vivo role of SENP3 in vascular remodeling, SENP3 +/− mice and wild-type (WT) littermates were subjected to partial ligation of left common carotid artery (LCCA).…”
Section: Resultsmentioning
confidence: 99%
“…As a member of the SUMO-specific protease family, the function of SENP3 is known to regulate deSUMOylation of chromosome-associated proteins and chromosome stability in multiple cellular biological processes. 26 , 27 Hypoxia is a common phenomenon in human solid tumors. Recent studies have shown that SENP3 is a sensitive redox sensor, as SENP3 upregulation in cells is triggered by oxidative modification and is responsible for HIF-1α transactivation.…”
Section: Discussionmentioning
confidence: 99%